If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2y) = 0 (x * 3 + -2y * 3) = 0 (3x + -6y) = 0 Solving 3x + -6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 3x + -6y + 6y = 0 + 6y Combine like terms: -6y + 6y = 0 3x + 0 = 0 + 6y 3x = 0 + 6y Remove the zero: 3x = 6y Divide each side by '3'. x = 2y Simplifying x = 2y
| 6/8=x | | 5XZ=1.50 | | 3x-(11)=34+2x | | -2-(3-5t)= | | 8x=4(7x+25) | | 2=2(k+3)+4(5-2k) | | (6+2i)(-4-3i)= | | 5x+4=10-x | | -20=-4a-6a | | 3/4(24-8b)=3(5b+1) | | (3x+2)-(2x-3)=-10 | | -4(4a-2)=88 | | 4-2(v-7)=-8 | | 4-4v=-(v+2) | | 17-x=23 | | 6(6b+2)=192 | | 6(y-3)=3y-30 | | (x+5)(x^2+10x+25)=0 | | 4(920-x)+2x=2446 | | 8z=12-28 | | 2x+36=4x | | 5(d+1)-4d=51-5d | | -6(-6r+3)-6=120 | | 2(6-10m)=10(2m-6) | | x+4+8x=4 | | 8+x=2x | | 23x+43-31+45=3254 | | 6x+9=x-8 | | 5(-6-4n)=-110 | | 4k^2-81=0 | | 2(-10m)=10(2m-6) | | 5r+7R+6R-6= |